Importance of the natural coagulant Opuntia Ficus-Indica for the removal of turbidity in water, in the period from 2012 to 2022: A review of the scientific literature (LACCEI, 2024)
Water pollution is a worldwide problem, which is why the use of traditional technologies is sought due to their potential and biodegradability, reducing the use of synthetic coagulants. That is why this research aims to identify the importance of the natural coagulant Opuntia Ficus-Indica for the removal of turbidity in waters worldwide according to the research journals of the database of the last ten years. Faced with this, information was consulted in repositories and in various databases such as: Scopus, ScienceDirect, Dialnet, Redalyc, Scielo, Alicia, Google Scholar, ProQuest, Researchgate and Iopscience. For the selection criteria of the articles and theses, the period 2012-2022 was considered, indexed journals, English and Spanish language, and that meet the research objective. Among the limitations is the slight information, private access and lack of knowledge of foreign languages. As a result, the highest turbidity removal was obtained with 99.56% and the lowest value with 50.5%. In summary, the natural coagulant Opuntia Ficus-Indica is important for its removal capacity, pH inalterability, biodegradable, without generation of toxic sludge and is not harmful to health.